Chapter 7 Made in France and Made in Paris Luxury branding in the longue durée - Pouillard, Veronique (Taylor & Francis, 2023)
Made in France examines the long history of the branding of the French nation, from the political imprint of Prime Minister Jean-Baptiste Colbert to the present day. The politics of Made in France were articulated at several levels of power, which was centralised by the French state, but also exercised locally, as in Paris and in the wine producing regions. The French government has consistently fostered production that advertised its country-of-origin as a symbol of quality on domestic and international markets. This chapter discusses the luxury industries, especially haute couture. The experiences of this industry, and other luxury industries show that is possible to relocate production outside France, which has resulted in the massification of luxury-item production.